Development and validation of bioanalytical assay methods for fentanyl in human plasma - Abay, Efrem Teclehaymanot (University of the Free State, 2004)
Abstract not available
Keywords: Gas Chromatography; High-Performance Liquid Chromatography; Nitrogen/Phosphorus selective detector (NPD); Mass spectrometer; Fentanyl; d5-fentanyl; Sufentanil; Method development; Validation; Liquid chromatography; Fentanyl -- Physiological effect; Analgesics; Drugs -- Research; Dissertation (M.Sc. (Chemistry))--University of the Free State, 2004